ARIMA-ARCH-Based Economic Growth Prediction for Lampung Province - Gitara Dhea Pramudita; Dedy Yuliawan (Citakonsultindo, 2026)
Economic growth is an important indicator of regional economic performance and is influenced by dynamic changes over time. This study aims to analyze the forecasting of economic growth in Lampung Province using the ARIMA-ARCH method. The study uses quarterly secondary data on Lampung Province's economic growth derived from Gross Regional Domestic Product (GRDP) at constant prices for the period 2010Q1–2025Q4. The analysis was conducted using the EViews 10 software through several stages, including stationarity testing, ARIMA model identification, parameter estimation, diagnostic testing, ARCH-LM testing, and the formation of the ARIMA-ARCH model. The results indicate that the ARIMA(1,0,0) model is the most appropriate model for describing the mean process of economic growth. The ARCH-LM test indicates the presence of conditional heteroskedasticity in the ARIMA residuals, so the analysis is continued using the ARCH model. The ARIMA(1,0,0)-ARCH(1) model is selected as the final model because the parameters are statistically significant and the model provides a parsimonious representation of the residual volatility. The resulting model is then used to forecast Lampung Province's economic growth for the period 2026Q1–2027Q4. The findings are expected to provide information that can support regional economic planning and policy formulation.